Melatonin biosynthesis and signal transduction in plants in response to environmental conditions - Liu, G.; Hu, Q.; Zhang, X.; Jiang, J.; Zhang, Y.; Zhang, Z.
Melatonin, the most widely distributed hormone in nature, plays important roles in plants. Many physiological processes in plants are linked to melatonin, including seed germination, anisotropic cell growth, and senescence. Compared to animals, different plants possess diverse melatonin biosynthetic routes and regulatory networks. Whereas melatonin biosynthesis is regulated by ambient signals in animals, little is known about how melatonin biosynthesis in plants responds to environmental signals. Plants are affected by numerous environmental factors such as light, temperature, moisture, carbon dioxide (CO2), soil conditions, and nutrient availability at all stages of development and in different tissues. Melatonin levels exhibit dynamic changes that affect plant growth and development. Melatonin plays various species-specific roles in plant responses to different environmental conditions. However, much remains to be learned, as not all environmental factors have been studied, and little is known about the mechanisms by which such factors influence melatonin biosynthesis. In this review, we provide a detailed, systematic description of melatonin biosynthesis and signaling and of the roles of melatonin in plant responses to different environmental factors, providing a reference for in-depth research on this important issue.
Keywords: MELATONIN; BIOSYNTHESIS; ENVIRONMENTAL FACTORS; PLANTS; SIGNAL TRANSDUCTION